Propuesta de diseño estructural de un tanque agitador vertical para la mezcla de biofertilizante (2020)
This document is a design study of a vertical agitator tank for mixing 100-liter natural fertilizer, a topic that was chosen as an integrative degree project for the title of mechanical engineer. This proposal is focused on the appropriate design of a shaker tank for a bio fertilizer mixture made by the Fertimax company based on the viscosity and density of the mixture. In this document within the theoretical framework there are also the basic concepts of stirring and mixing. In the chapters you will find main types and characteristics of agitated tanks such as, types of tanks, types of flow, types of impeller, with their main characteristics. The calculations for the structural design of the agitator tank were defined and carried out, and finally, the materialization costs of the agitator tank were defined.